Peran Kompetensi dalam Memediasi Pengaruh Pengelolaan Sumber Daya Manusia dan Kompensasi Terhadap Kinerja Karyawan Pada PT Izza Elektrika Inspeksi Solusindo (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to describe and analyze how competency mediates the influence of human resource management and compensation on employee performance at PT Izza Elektrika Inspeksi Solusindo. The population of this study consists of all employees. Data were collected using a questionnaire distributed to 150 respondents. The sampling method employed was purposive sampling. Data were analyzed using the Smart PLS software. The findings reveal that human resource management has a positive and significant effect on competency, as well as a similar positive and significant impact on employee performance. Compensation also contributes positively and significantly to both competency and employee performance. Furthermore, competency has a positive and significant effect on employee performance and acts as a mediator in the relationship between human resource management and employee performance, as well as between compensation and employee performance